Comparison of qPCR versus culture for the detection and quantification of Clostridium difficile environmental contamination - MacDougall, Laura K.; Broukhanski, George; Simor, Andrew; Johnstone, Jennie; Mubareka, Samira; McGeer, Allison; Daneman, Nick; Garber, Gary; Brown, Kevin A. (PloS one, 2018)
Contaminated surfaces serve as an important reservoir for Clostridium difficile transmission. Current strategies to detect environmental contamination of C. difficile rely heavily on culture, and often only indicate presence versus absence of spores. The goal of this study was to compare quantitative PCR (qPCR) to culture for the detection and quantification of C. difficile from inert surfaces. First, we compared the limit of detection (LOD) of a 16S rRNA gene and toxin B gene qPCR assay for detection of C. difficile in solution. Second, we compared the LODs of 16S rRNA gene qPCR versus culture for detection of C. difficile from surfaces. Solution experiments were performed by direct seeding of spores into neutralizing broth, whereas surface experiments involved seeding of spores onto plastic test surfaces, and recovery using sponge swabs. Both experiments were conducted using spores expressing short (NAP1) and long (NAP4) hair lengths. Combining data from both strains, the overall LOD for C. difficile cells in solution was 1.4 cells for 16S rRNA gene and 23.6 cells for toxin B gene qPCR (p<0.001). The overall LOD for C. difficile cells from surfaces was 17.1 cells for 16S rRNA gene qPCR and 54.5 cells for culture (p = 0.05), and was not statistically different between strains for each method (p = 0.52). Overall, the proportion of C. difficile cells recovered from surfaces was good when detected by 16S rRNA gene qPCR and culture (qPCR: 76%, culture: 67%, p = 0.36), but, 16S rRNA gene qPCR was capable of detecting lower levels of surface contamination. Future work attempting to measure the presence of C. difficile on environmental surfaces should consider using qPCR.